FORECASTING HIV PREVALENCE AMONG INDIVIDUALS AGED 15-49 YEARS IN SOUTH AFRICA USING HOLT’S LINEAR METHOD - Dr. Smartson. P. NYONI; Thabani NYONI (European Science Publishing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for South Africa from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.6 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will slightly decline over the out of sample period but still remain high. Therefore, we encourage authorities to scale up HIV testing, increase ART coverage and strengthen HIV prevention among this age group.
Keywords: Exponential smoothing, Forecasting, HIV prevalence